Behaviorist-Based Cooperative Learning as a Strategy to Enhance Islamic Education Performance: Evidence from Fifth-Grade Students - Putra, Firsta Pramudita Utomo; Arjiman (Nizham Jurnal Studi Keislaman, 2025)
This study aims to analyze the application of behaviorist learning theory through the cooperative learning model in improving Islamic Education (PAI) learning outcomes for fifth-grade elementary school students. The background of this research is the low student participation and achievement in PAI lessons. This research uses a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation. The results show that the implementation of cooperative learning based on behaviorist principles such as reinforcement and punishment can improve students’ learning motivation, engagement, and academic achievement. These findings highlight the importance of integrating learning theory with cooperative strategies in the teaching of PAI at the elementary level.